Forensic genetics in the governance of crime (2020)
The introductory chapter offers a detailed description of the themes that the reader can expect to find in this book, and a discussion of the social and academic relevance of the role and use of forensic genetic technologies in the criminal justice system. This introductory chapter provides the key concepts for the discussion of how developments in the application of forensic genetics can be understood as part of wider shifts in how the governance of criminality is enacted and made visible through the symbolic power invested in science and technology.